2006
DOI: 10.1620/tjem.208.41
|View full text |Cite
|
Sign up to set email alerts
|

Atopy in Patients with Bronchiectasis: More than Coincidence

Abstract: Bronchiectasis is common in developing countries, but its precise underlying mechanism can be detected in only about 40% of the cases. The studies reporting the frequency of atopy and its relation to radiological findings and lung function in bronchiectasis are limited in number, and the results are controversial. The present study was designed to investigate the relationship between atopy and bronchiectasis by means of high resolution computed tomography (HRCT) and pulmonary function tests. Skin prick test, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Nonspecific vaginal hypersensitivity, which can be triggered by nonallergic factors as in other target organs of the allergy, may be another pathogenetic mechanism of allergic vulvoginitis 1 . Recurrent bacterial, viral and parasitic infections may be likely to induce atopy and hypersensitivity as suggested previously 20 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nonspecific vaginal hypersensitivity, which can be triggered by nonallergic factors as in other target organs of the allergy, may be another pathogenetic mechanism of allergic vulvoginitis 1 . Recurrent bacterial, viral and parasitic infections may be likely to induce atopy and hypersensitivity as suggested previously 20 …”
Section: Discussionmentioning
confidence: 79%
“…1 Recurrent bacterial, viral and parasitic infections may be likely to induce atopy and hypersensitivity as suggested previously. 20 To our knowledge, this study has demonstrated the association of atopy and RVV with undetermined etiology for the first time in the published literature, as patients with recurrent vaginal candidiasis were mostly included in other studies dealing with the issue. [3][4][5][6] Although SPT is a valuable and useful diagnostic tool to document atopy in daily medical practice, we must admit that lack of vaginal provocation test during an asymptomatic period, determination of total and specific IgE levels and eosinophil count in blood and vaginal smears as limitations of our study.…”
Section: Discussionmentioning
confidence: 80%
“…Male N (%) 4 (50) 6 (50) 19 (45) F508 homozygous N (%) 3 (37) 6 (50) 24 (57) F508 heterozygous N (%) 4 (50) 5 (41) 11 (26) Other/Other N (%) 1 (12) 1 (8) 7 (16) Atopic a N (%) 6 (75)* 6 (50)* 11 (26) Number of positive skin tests b N ± SD 3.0 ± 1.5 A high rate of atopy of up to 40% has been reported in adults with CF, 23 we found a similar prevalence among our pediatric population at 37%. It is not clear why atopy is more prevalent in CF than the general population, however, as high rates have also been found in non-CF bronchiectasis 24 it is likely related to chronic airway inflammation, increased epithelial permeability and greater access for aeroallergens into the bronchial mucosa. 25 Similar to findings by Nepomuceno et al, 26 we found that ABPA rates were higher amongst atopic than nonatopic patients (26% vs 5.1%), therefore determination of atopic status with closer surveillance for ABPA in this group of patients is warranted in the clinical setting.…”
Section: Resultsmentioning
confidence: 99%
“…Bronşektazili hastalardaki atopi sıklığı %10-54 arasında değişmektedir (20). Çalışmamızda 4 (%11.4) hastada atopi saptandı.…”
Section: Gereç Ve Yöntemunclassified